2012
DOI: 10.7314/apjcp.2012.13.7.3191
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Insulin-like Growth Factor-2 Expression and Prognosis after Transcatheter Arterial Chemoembolization and Octreotide in Patients with Hepatocellar Carcinoma

Abstract: Objective: To investigate the association between the change of IGF-2 level in serum after transcatheter arterial chemoembolization (TACE) and hepatocellular carcinoma (HCC) progression, especially in relation to metastasis. Methods: IGF-2 in serum was measured by quantitative sandwich enzyme-linked immunosorbent assaybefore, 3 days and 4 weeks after TACE in 60 patients with HCC. The occurrence of HCC metastasis was also evaluated, 3 months after TACE. Results: (1) The average serum level of IGF-2 in the 60 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Soon et al reported that high miR-483-5p expression predicted for poor overall specific survival in adrenocortical carcinomas [ 31 ]; Chabre et al also found that high serum miR-483-5p level was associated with both shorter recurrence-free survival and shorter overall survival in adrenocortical cancer patients [ 32 ]; similarly, Wang et al reported that high serum miR-483-5p concentration was related to poor survival outcome in patients with nasopharyngeal carcinoma [ 47 ]. On the other hand, Dong et al reported that serum IGF-II level was correlated with extrahepatic metastases in HCC patients [ 48 ]; Xion et al observed that the increase of IGF-II level in serum appeared to be associated with the occurrence of metastatic HCC after TACE and chemotherapy [ 49 ]; Sayer et al found that high IGF-II expression was an independent predictor of poor survival in patients with epithelial ovarian cancer [ 50 ]. The above findings indicate that the overexpression of both miR-483-5p and IGF-II may be associated with poor clinical outcome in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Soon et al reported that high miR-483-5p expression predicted for poor overall specific survival in adrenocortical carcinomas [ 31 ]; Chabre et al also found that high serum miR-483-5p level was associated with both shorter recurrence-free survival and shorter overall survival in adrenocortical cancer patients [ 32 ]; similarly, Wang et al reported that high serum miR-483-5p concentration was related to poor survival outcome in patients with nasopharyngeal carcinoma [ 47 ]. On the other hand, Dong et al reported that serum IGF-II level was correlated with extrahepatic metastases in HCC patients [ 48 ]; Xion et al observed that the increase of IGF-II level in serum appeared to be associated with the occurrence of metastatic HCC after TACE and chemotherapy [ 49 ]; Sayer et al found that high IGF-II expression was an independent predictor of poor survival in patients with epithelial ovarian cancer [ 50 ]. The above findings indicate that the overexpression of both miR-483-5p and IGF-II may be associated with poor clinical outcome in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor genetics vary in HCC and multiple genetic markers have been associated with tumor progression and recurrence (15-17). Recent reports further reveal that TACE and RFA affect molecular markers related to tumor aggressiveness and thus MMT may serve to uncover and, in certain cases, alter the underlying tumor biology (18,19). Clinically, patients presenting with higher tumor stage and AFP usually do not progress to transplant due to concerns that they harbor more advanced and biologically active tumors (20).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it would be interesting in future to see if there are additional differences between viral and alcoholic related HCC like differential expression of receptors or production of trophic factors. In a recent study an increase of serum IGF2 level was reported to be associated with the occurrence of HCC metastasis after TACE and octreotide, as metastatic foci were found in 97% when IGF2 was increasing in contrast to only 13.6% of patients with an IGF2 decrease [141] . In the context of the previous discussion, it should be noted that the expression of IGF2 in HCC was strongly associated with HBV infection [142] .…”
Section: Resultsmentioning
confidence: 94%